Comparación de tres métodos de extracción de aceite de Mauritia flexuosa aplicados por productores de la Amazonía Peruana 2023 - Paima Pizango, Luis Martin (2024)
This study investigates three methods of oil extraction from Mauritia flexuosa used by producers in the Peruvian Amazon, using three varieties of aguaje: Color, Amarillo and Shambo Azul. The study was descriptive-comparative, the first method consisted of pressing the flour obtained from the aguaje pulp, bagasse and husk (DSMP); the second method consisted of pressing the aguaje pulp flour (DSP); for the third method the procedure consisted of bringing the wet aguaje pulp to boiling for a period of 30 minutes (DC). The findings reveal that the Mauritia flexuosa varieties with the highest oil content irrespective of the method employed are Color and Amarillo, with 26.7% and 26.03%e for the DSMP method; 18.3%e and 18% for the DSP method; 17.4% and 15% in the DC method. The method of pressing the flour obtained from the pulp, bagasse and husk of the aguaje (DSMP) presented the highest yield in the three varieties, for the varieties Color and Amarillo resulted in an average of 28% and for the Shambo Azul 19.7%. In conclusion, the extraction method by which the highest oil yield can be obtained from Mauritia flexuosa is the pressing method of pulp meal, bagasse and husk. And either the Color or Amarillo varieties can be used as both have good yields.